The Humanistic Side of Prostitution in Garry Marshall's Pretty Woman Movie : A Sosiological Literary Criticism - NINGSIH, SRI (2011)
The object of the study is Garry Marshallmovie, written by JF. Lawton. This study describes the companionship is more important than sexual satisfaction. Edward and Vivian enjoyed their companionship better than physically enjoyment. Marshall put the characters in such a setting that permits him to build an interesting plot. The structural elements of the movie are related to one another forming a unified whole. The objective of the study is to analyze the movie based on its structural elements and the sociological analysis. In analyzing Garry Marshall, the researcher uses sociological literary criticism approach. The data sources are primary and secondary data. The primary data source and the object of this study is the movie of Garry Marshallitself. Produced in 1990 by touchstone pictures and the secondary data are the other references related to the analysis such as the other biography and virtual references. The method of the data collection is literary research. The technique of data analysis is descriptive. The outcome of the study shows the following conclusion. First, literary works may reflect the social reality. Second, Garry Marshall wants to say that the companionship is more important than sexual satisfaction. Third, Garry Marshall wants to criticize some circles of society.